Facilitation of PdPb nanoalloy anchored on rGO/MOF-derived δ-Ga2O3 nanorod for electrocatalytic oxidation of methanol, ethanol and ethylene glycol. (10th March 2022) - Zhong, Yuting; Hu, Yalan; Mo, Han; Wu, Zhirui; Fu, Xin; Zhou, Liqun; Liu, Hongying; Li, Ling; Liu, Xiaoguang
Highlights: rGO/MOF-derived Ga2 O3 nanorod anchored PdPb nanoalloy composite was prepared. PdPb@rGO/Ga2 O3 displays excellent electrocatalytic activity and stability for MOR, EOR and EGOR. The outstanding performance is attributed to the combined action of PdPb alloy and rGO/Ga2 O3 . Oxidation mechanisms of three alcohols and removal processes of adsorbed CO were proposed. Abstract: A wrinkled rGO modified nanorod gallium oxides (Ga2 O3 ) anchored PdPb nanoalloys composite (PdPb@rGO/Ga2 O3 ) was prepared using GO/Ga-MOF as the precursor by facile hydrothermal, calcination and reduction approach, and then applied as an electrocatalyst for alcohols electrooxidation. Electrochemical tests show that the fabricated PdPb@rGO/Ga2 O3 exhibits superior electrocatalytic activity and high anti-CO poisoning capability for methanol, ethanol and ethylene glycol oxidation reactions (MOR, EOR and EGOR), outperforming Pd@rGO/Ga2 O3 and commercial Pd/C. Specifically, the bimetallic electrocatalyst owns the highest forward peak current density of 115.84 mA cm −2, 146.97 mA cm −2 and 226.59 mA cm −2, which is 4.69, 5.08 and 8.38 times of Pd/C for MOR, EOR and EGOR, respectively. After 3600 s CA test, the retained current density of PdPb@rGO/Ga2 O3 achieves the initial 59.24%, 71.13% and 81.71% towards MOR, EOR and EGOR, respectively. The remarkable performance is attributed to the electronic effects of PdPb nanoalloys, which can improve the electronic structure of Pd d-band, while the surface decoration of Pb/PbO NPs can dramatically adsorb more oxy-species and accelerate the oxidative removal of CO(ads) . Moreover, the oxidation mechanisms of three alcohols and the removal processes of CO(ads) on the Pd surface are analyzed in detail.